2022
DOI: 10.1017/sjp.2022.19
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulated Learning and Working Memory Determine Problem-Solving Accuracy in Math

Abstract: This study aims to understand the role of self-regulated learning (SRL) and its different processes in the relationship between working memory (WM) and problem-solving accuracy in math in primary school children. A sample of 269 primary school children (Mage = 8.84, SD = 0.81, 58% boys) participated in this study. Tasks were used as intervention resources to assess children’s WM (i.e., reading and computation span tasks), SRL (i.e., a digital game), and performance (i.e., the performance in the game, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…For example, Arfé et al (2020, p. 6) emphasize the suitability of computational thinking for the students’ development of cognitive control, with coding tasks performed by the students analyzed according to “measures of executive functioning”. Similarly, Ferreira et al (2022, p. 13) discuss mathematics tasks based on measures relating to EF, stating that “improving math performance may actually lead to improvements in executive functions and vice versa”.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Arfé et al (2020, p. 6) emphasize the suitability of computational thinking for the students’ development of cognitive control, with coding tasks performed by the students analyzed according to “measures of executive functioning”. Similarly, Ferreira et al (2022, p. 13) discuss mathematics tasks based on measures relating to EF, stating that “improving math performance may actually lead to improvements in executive functions and vice versa”.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, intervention examples with strategies to extend time on tasks through methods such as mindfulness training, adaptive learning technologies, and exercises for eye movement training seemed to affect EF support positively (Chan et al, 2022; Molenaar et al, 2019; Qushem et al, 2022; Vekety et al, 2022; Zhou et al, 2021). Generally, mathematics and language were the most commonly studied curriculum topics and were sometimes discussed as directly improving EF (e.g., Ferreira et al, 2022). Thus, such methods and curriculum topics may also considered as appropriate to emphasize in special education.…”
Section: Discussionmentioning
confidence: 99%
“…This study, however, concluded that self-regulated learning does not have a significant effect on students' problem-solving abilities. However, in other studies, it has been elucidated that self-regulated learning can indirectly enhance the accuracy of mathematical problem-solving by utilizing working memory during the execution of selfdirected learning (Ferreira et al, 2022). The success of learning can be assessed through students' achievements in problem-solving and self-regulation regarding task-related activities by orienting themselves towards the tasks (Corte, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Students' ability to pay attention, follow instructions carefully, produce work that is appropriate for expectations, or effectively use language to accomplish other learning objectives are all important components of learning. It is thought to be intriguing and useful if employed (Ferreira et al, 2022;Laelasari, 2018;Sa'id et al, 2021). One | 1199 of the objectives of realistic education is to get students to switch from abstract to more realistic materials so that teachers can use various examples and props of the environment to help students understand encourage (Royhana et al, 2021).…”
Section: Introductionmentioning
confidence: 99%